2015
DOI: 10.1063/1.4931059
|View full text |Cite
|
Sign up to set email alerts
|

Various notions of positivity for bi-linear maps and applications to tri-partite entanglement

Abstract: Abstract. We consider bi-linear analogues of s-positivity for linear maps. The dual objects of these notions can be described in terms of Schimdt ranks for tritensor products and Schmidt numbers for tri-partite quantum states. These tripartite versions of Schmidt numbers cover various kinds of bi-separability, and so we may interpret witnesses for those in terms of bi-linear maps. We give concrete examples of witnesses for various kinds of three qubit entanglement.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…If ̺ is GHZ diagonal, then we have ∆ ̺ = min{a 1 , a 2 , a 3 , a 4 }. The number C(z) above turns out to coincide essentially with the number in the characterization of three qubit X-shaped entanglement witnesses [21]. In this way, we got a simpler expression for C(z).…”
Section: Ghz Diagonal Statesmentioning
confidence: 81%
See 1 more Smart Citation
“…If ̺ is GHZ diagonal, then we have ∆ ̺ = min{a 1 , a 2 , a 3 , a 4 }. The number C(z) above turns out to coincide essentially with the number in the characterization of three qubit X-shaped entanglement witnesses [21]. In this way, we got a simpler expression for C(z).…”
Section: Ghz Diagonal Statesmentioning
confidence: 81%
“…For a three qubit X-shaped self-adjoint matrix W = X(s, t, u), the authors [21] have shown that W = X(s, t, u) is an entanglement witness if and only if it is non-positive and satisfies the inequality…”
Section: Entanglement Witnessesmentioning
confidence: 99%
“…In other words, detecting entanglement with the PPT property depends on the anti-diagonal phases. It was shown in [17,19] that the anti-diagonal phases also play a role to characterize three-qubit X-shaped entanglement witnesses.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the number in the right side of (7) appear in the characterization of X-shaped three-qubit entanglement witnesses [17], which correspond to positive bi-linear maps between 2 × 2 matrices [25]. In order to get a preliminary criterion, we introduce the number…”
Section: Separability Criterion With Anti-diagonal Phasesmentioning
confidence: 99%
See 1 more Smart Citation